2008
DOI: 10.1007/s12301-008-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Traitement des sténoses de l’urètre par urétrotomie interne endoscopique: résultats anatomiques et fonctionnels d’une série de 244 cas

Abstract: Le rétrécissement urétral est la diminution de la lumière urétrale, voire son oblitération complète. Il entraîne, de ce fait, une dysurie chronique. En Afrique, il représente une complication tardive des infections sexuellement transmissibles 1 .Il n'y est donc pas rare. Son diagnostic est évoqué par la clinique devant des antécédents infectieux ou traumatiques et est confirmé

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
3
2
0
Order By: Relevance
“…This finding is similar to that of other authors on the African continent, Ngaroua in Cameroon 70.17% [6], Hounnasso in Togo 48.1% [3], and Benjelloun in Morocco 82% [4]. Dysuria is explained by the fact that urethral stricture is a reduction in the lumen of the urethra resulting in an obstacle to the flow of urine out of the bladder.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding is similar to that of other authors on the African continent, Ngaroua in Cameroon 70.17% [6], Hounnasso in Togo 48.1% [3], and Benjelloun in Morocco 82% [4]. Dysuria is explained by the fact that urethral stricture is a reduction in the lumen of the urethra resulting in an obstacle to the flow of urine out of the bladder.…”
Section: Discussionsupporting
confidence: 90%
“…However, in developed countries, iatrogenic causes are most often due to endoscopic maneuver [7] [8] [9]. In our study, analysis of the characteristics of urethral strictures revealed the following: the strictures were essentially bulbar (81.54%), single (55.79%) and short (68.6%), as in the series by Benjelloun et al in Morocco [4], Hounnasso in Togo [3], Moby in Cameroon [2] and Ndour in Senegal [10]. On the other hand, Zongo et al in Burkina Faso reported a predominance of long and multiple strictures, respectively 69% and 75% [11].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In developed countries, the iatrogenic etiology dominates; while in developing countries, notably in Senegal, infection causes predominate [1] [2].…”
Section: Introductionmentioning
confidence: 99%